Effect of aerobic exercise training on General Health indices in Inactive Veterans - A. Tofighi; J. Nozad; S. Babaee; S. Dastah (Afarand Scholarly Publishing Institute, 2013)
Background and aims: Nowadays many countries use exercise as one of the treatment procedure in improving of physical and psychological health of veterans, so it has been effective results yet. The aim of this study was to examine the effect of aerobic exercise on general health and depression of veterans. Material and method: Based on a semi experimental design 40 veterans, grade range 25 to 70 percent and with age average 40/3±1/4, were selected and randomly divided into two experimental and control groups. Subjects in the experimental group participated in a period of 12 weeks aerobic exercise training program, which done five times a week at50-65 percent of Vo2max. Control group did not participate in any exercise program during study period. General health of the subjects and its subscales was measured by the General Health Questionnaire (GHQ). Also for determine of depression range Serotonin levels were assayed before and after training for both groups. T student t test was used for comparison between two groups and data were analyzed by using of SPSS software version 18 at P<0.05. Results: Data analysis showed a significant difference between‌ the two groups in general health. The difference in psychosomatic subscales, anxiety and in somnia, social dysfunction and depression were observed between the two groups (p<0.05). Conclusion: Aerobic exercise for inactive veterans may be effective in reducing depression and increasing general health and placed in line health promotion programs.